Numerical simulation of stress amplification induced by crack interaction in human femur bone - Noor Alia Md Zain (Institute of Engineering Mathematics, University Malaysia Perlis, 2014)
This research is about numerical simulation using computational method which study on stressamplification induced by crack interaction in human femur bone.Crack in human femur bone usually occur because of large load or stress applied on it. Usually, the fracture takes longer time to heal itself. The crack interaction is still not well understood due to bone complexity. Thus, brittle fracture behaviour of bone may be underestimated and inaccurate. This study aims in investigating the geometrical effect of double co-planar edge cracks on stress intensity factor (K) in femur bone.